2023
DOI: 10.3390/su15032180
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Effects of Growth Mindset on Students’ Intention toward Self-Regulated Learning during the COVID-19 Pandemic: A PLS-SEM Approach

Abstract: The COVID-19 pandemic has brought unprecedented challenges to students’ learning processes in higher education. This study aimed to investigate the effects of a growth mindset on university students’ intention toward self-regulated learning during the COVID-19 pandemic. The theoretical model was proposed based on the Theory of Planned Behavior, along with two additional dimensions: growth mindset and perceived teacher support. The developed model was validated by adopting a partial least squares structural equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Partial least squares structural equation modeling requires a two-stage testing process, including measurement model assessment and structural model assessment ( Anderson and Gerbing, 1988 ). The first stage is mainly for the outer model testing, such as the reliability, the convergent validity testing, and the discriminant validity testing of each construct ( Jiang et al, 2023 ). Previous studies suggested that each indicator’s factor loadings must exceed 0.6; each factor’s reliability (CR, Cronbach’s α, and rho-A ) must exceed 0.6; and each factor’s average variance extracted (AVE) must exceed 0.5 ( Fornell and Larcker, 1981 ; Hair et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial least squares structural equation modeling requires a two-stage testing process, including measurement model assessment and structural model assessment ( Anderson and Gerbing, 1988 ). The first stage is mainly for the outer model testing, such as the reliability, the convergent validity testing, and the discriminant validity testing of each construct ( Jiang et al, 2023 ). Previous studies suggested that each indicator’s factor loadings must exceed 0.6; each factor’s reliability (CR, Cronbach’s α, and rho-A ) must exceed 0.6; and each factor’s average variance extracted (AVE) must exceed 0.5 ( Fornell and Larcker, 1981 ; Hair et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…The existence of differences between constructs was evaluated by utilizing the discriminant validity test ( Jiang et al, 2023 ). The Fornell-Larcker criterion matrix ( Hu et al, 2022 ), as illustrated in Table 5 , is a method commonly used to ascertain discriminant validity.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, in Jiang and collaborators research (Jiang et al, 2023), an extended model of the planned behavior theory was employed, utilizing a PLS-SEM approach to investigate the direct, indirect, mediating, and moderating roles of students' growth mindset in self-regulated learning intention during the COVID-19 pandemic. Their findings affirmed the positive influence of students' growth mindset on this learning process, whether through planned behavioral control, students' learning attitude, or the direct path to self-regulated learning intention.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The results showed that self-regulated learning was positively associated with both growth mindset and academic motivation, suggesting that promoting self-regulated learning could help cultivate motivational resilience. A study by Jiang et al (2023) [51] examined the relationship between growth mindset, self-regulated learning, and academic achievement in Chinese university students. The findings revealed that both growth mindset and self-regulated learning were positively associated with academic achievement, highlighting the importance of promoting these two factors in supporting students' academic success.…”
Section: Growth Mindset and Self-regulated Learning For Cultivating M...mentioning
confidence: 99%